The diagnostic pathway in complex paediatric neurology: A cost analysis. (March 2015) - van Nimwegen, K.J.M.; Schieving, J.H.; Willemsen, M.A.A.P.; Veltman, J.A.; van der Burg, S.; van der Wilt, G.J.; Grutters, J.P.C.
Abstract: Background: The diagnostic trajectory of complex paediatric neurology may be long, burdensome, and expensive while its diagnostic yield is frequently modest. Improvement in this trajectory is desirable and might be achieved by innovations such as whole exome sequencing. In order to explore the consequences of implementing them, it is important to map the current pathway. To that end, this study assessed the healthcare resource use and associated costs in this diagnostic trajectory in the Netherlands. Methods: Fifty patients presenting with complex paediatric neurological disorders of a suspected genetic origin were included between September 2011 and March 2012. Data on their healthcare resource utilization were collected from the hospital medical charts. Unit prices were obtained from the Dutch Healthcare Authority, the Dutch Healthcare Insurance Board, and the financial administration of the hospital. Bootstrap simulations were performed to determine mean quantities and costs. Results: The mean duration of the diagnostic trajectory was 40 months. A diagnosis was established in 6% of the patients. On average, patients made 16 physician visits, underwent four imaging and two neurophysiologic tests, and had eight genetic and 16 other tests. Mean bootstrapped costs per patient amounted to €12, 475, of which 43% was for genetic tests (€5, 321) and 25% for hospital visits (€3, 112). Conclusion: Currently, the diagnostic trajectories of paediatric patients who have complex neurological disease with a strong suspected genetic component are lengthy, resource-intensive, and low-yield. The data from this study provide a backdrop against which the introduction of novel techniques such as whole exome sequencing should be evaluated.